Hubungan Tingkat Kepatuhan dengan Tingkat Kekambuhan Gangguan Jiwa Puskesmas Sepatan dan Kedaung Tangerang Tahun 2020 - Amran Sebayang (Syntax Corporation Indonesia, 2021)
In patients with mental disorders, almost all patients experience recurrence repeatedly. Data from medical records at the Sepatan Health Center, the presentation of recurrence of mental illness patients at the Sepatan Health Center in 2019 was 26.8%. The same was true for the Kedaung Barat Puskesmas at 22%. To determine the relationship between the level of control adherence and the recurrence rate of mental disorders clients at the Sepatan Public Health Center and the Kedaung Barat Tangerang Public Health Center in 2020. Including an analytical survey with a cross sectional approach. The population in this study were all schizophenia patients at the Sepatan Health Center and the Kedaung Barat Health Center, Tangerang Regency in 2020, as many as 109 people. Samples were taken based on the slovin as many as 109 respondents. This study used univariate and bivariate analysis with the Chi Square test. Based on univariate analysis of 109 people, the majority with mental disorders clients who did not relapse were 58 people (53.2%), and the adherence level of adherent controls was 61 people (56%). The results of the bivariate analysis with the chi square test found that there was a relationship between control compliance (p-value 0.000), with mental disorders client recurrence. There is a relationship between the level of control adherence with the recurrence rate of mental disorders clients, with a possible rate of 29,871. It is hoped that it can provide information and be able to provide education on nursing services, especially for the client's family of mental disorders to motivate clients with mental disorders to comply with control.